GERAKAN LITERASI BERBASIS TEKNOLOGI: TRANSFORMASI PEMBELAJARAN DI MI NURUL HIDAYAH BOJONEGORO - Cindarbumi, Festian; Kurniawati, Naning; Sari, Astrid Chandra (Jurnal Abdi Insani, 2025)
The advancement of technology requires the education sector to continuously adapt, including MI Nurul Hidayah in Bojonegoro. The school still faces challenges such as low reading interest and limited access to digital learning media. These issues affect the effectiveness of the teaching and learning process. A technology-based literacy movement serves as a solution to enhance teachers’ and students’ competencies in utilizing digital media effectively. This Pelatihanaims to integrate technology into the learning process to improve digital literacy. The transformation is expected to foster a more inclusive literacy culture in the school environment. The implementation methods include teacher training on digital media use and instructional material development. The Pelatihanalso involves student mentoring and the introduction of various digital platforms such as reading apps and e-learning tools. All activities were carried out gradually and systematically. The results show a significant increase in students' reading interest, with 85% actively using the introduced digital library. Teachers improved their skills in designing technology-based instructional materials, utilizing educational applications and e-learning platforms. In addition, parental involvement in supporting children's literacy increased through socialization efforts. The learning environment became more interactive and engaging. Overall, the Pelatihansuccessfully fostered collaboration among teachers, students, and parents in building a sustainable digital literacy culture. It strengthened digital literacy and expanded access to interactive and continuous learning for MI Nurul Hidayah.